Sustainable Construction of Heterocyclic 1,2,3-Triazoles by Strict Click [3+2] Cycloaddition Reactions Between Azides and Alkynes on Copper/Carbon in Water - Aflak, Noura; Ben El Ayouchia, Hicham; Bahsis, Lahoucine; El Mouchtari, El Mountassir; Julve, Miguel; Rafqah, Salah; Anane, Hafid; Stiriba, Salah-Eddine (Frontiers in Chemistry, 2019)
1,4-Disubstituted-1,2,3-triazoles, considered as an important and useful class of heterocycles with potential applications in material science and biology, have been prepared in an efficient and selective manner by copper on carbon-catalyzed [3+2] cycloaddition reactions of azides and alkynes (CuAAC) in water under strict click chemistry conditions. Copper(I) catalysts heterogenized onto commercially activated carbon materials (Cu-CC) and on another carbon material produced from vegetable biomass using Argan nut shells (Cu-CANS) were found to be versatile catalytic sources for sustainable CuAAC. These copper on carbon supports were prepared and fully characterized by using two types of activated carbons that exhibit different porosity and specific surface. The delineation of the nature of the catalytic copper species and the role of the carbon support in the CuAAC were addressed. These heterogeneous copper on carbon catalysts were recovered and reused until ten catalytic runs without any noticeable loss of activity.